"To Be On Stage Means To Be Alive" Theatre Work with Education Undergraduates as a Promoter of Students' Mental Resilience. (3rd December 2015) - Harari, Michal Doron
Abstract: This article forms part of a research based on the Being Onstage Interventional Program (BIP) that utilizes therapeutic theatre work with the objective of strengthening undergraduate Education students' resilience. The working principles of BIP consist of the actor's work, group work, improvisations and repeated autobiographical performances. This article shall discuss the rationale of theoretical integration between resilience elements) and theatre work and Dramatherapy. The article includes a description of resilience. And theatrical practices like: BASIC Ph (Lahad), the Theory of Resource Conservation (Hobfoll) and Role Theory (Landy), the Theatre of Self Discovery (Emunah).